Avaliação do perfil de expressão e possíveis funções biológicas de RGMA em células satélites cultivadas in vitro - Christhiam Douglas Caetano Ribeiro (2023)
RGMa is a member of the family of repulsive guidance molecules, which were originally described as cues for the guidance of forming axons. New studies also point to RGMa in the development, maintenance and growth of skeletal muscles. Transcripts of this molecule were detected in pioneer cells, from the somites to the adult cell, where RGMa was detected in the sarcolemma and with a striated pattern in the sarcoplasm, similar to sarcomeric proteins. Overexpression of RGMa in adult muscle cells, of the C2C12 lineage, induced the formation of hypertrophic and hyperplastic cells compared to RGMa knockdown, which resulted in the opposite phenotype. In view of these findings, this work aimed to investigate the possible association of RGMa with satellite cells, evaluating (i) the expression pattern of this axon guide in satellite cells isolated from mice and cultured in vitro and (ii) its role during the phases of cell proliferation and differentiation. Satellite cells were isolated from digested myofibers of the EDL muscle of C57BL/6 mice. The expression pattern was determined by immunofluorescence of the cells, during the proliferation and differentiation stages. RGMa knockdown in these cells was induced by the RNA interference method, and the effects were assessed on satellite cell viability and proliferation. The expression pattern revealed the presence of RGMa predominantly in the nucleus of satellite cells, both in the proliferation and differentiation stages. The knockdown of RGMa in these cells induced a decrease in cell viability and the proliferative capacity of these cells in culture, always compared to the control group. Together, our results revealed that, RGMa is present in the satellite cell nucleus, where it possibly performs functions associated with satellite cell viability and proliferation. Therefore, this study contributed to revealing a new factor, associated with the proliferation of adult muscle stem cells, which could be used as a therapeutic target in the treatment of muscular myopathies; or for the selection of animals for greater meat production.